Control process development on the ground of project value dynamics laws - Bugrov, Olexander; Bugrova, Olena (Technology audit and production reserves, 2020)
The object of research is a conceptual approach to the process of controlling the dynamics of the financial and economic efficiency of a construction project as a result of engineering has been developed. Acceleration of scientific and technological progress underlines the relevance of this topic. It is established that the theory of the project value dynamics is based on three laws. The first law of the project value dynamics emphasizes that a qualitative, dynamic growth of value occurs only through innovation or rationalization, and the rest of the design changes is static. Charts of isovalue demonstrate the potential state of the financial and economic performance of the project in the four-dimensional space «time-benefits-costs-risks». Each subsequent line of isovalue, which runs farther from the origin, reflects a higher level of intense project value. The second law of value dynamics indicates that entropy is gradually decreasing as a result of the project. Thus, the earlier engineering sessions take place (within the project life cycle) for introducing innovations, the higher the potential for influencing the dynamics of the project value. The third law of the project value dynamics provides that the absolute maximum value cannot be achieved. So, innovation, unlike other factors of financial and economic growth, is an inexhaustible source of increasing the value of projects. The change in the «benefit-cost ratio» (BCR) adequately reflects the project value dynamics. This indicator clearly takes into account all four factors (measurements) of project effectiveness and captures precisely dynamic, qualitative changes in value. BCR is very similar to the definition of value, which is used in functional value and hierarchical analysis. This promotes mutual understanding and convergence in communications between project stakeholders (in the integrated Crystal model, value management). The process of controlling the project value dynamics directs the work of the engineering team to achieve project results that are best suited to the interests of investors, subject to a careful attitude to nature.